Could someone help me with this problem. I am coming up with 1/((sqrt(4x^2-1))+1) and it is wrong. Thanks
Okay !
First, you should calculate the derivative of u(x), namely $\displaystyle \sqrt{4x^2-1}$
You'll have to use the chain rule once again !
That is $\displaystyle (\sqrt{v(x)})'=\frac{v'(x)}{2 \sqrt{v(x)}}$
$\displaystyle u'(x)=\left(\sqrt{4x^2-1}\right)'=\frac{8x}{2 \sqrt{4x^2-1}}=\frac{4x}{\sqrt{4x^2-1}}$
Does it help ?
If not, I'd suggest you have a look here : Chain rule - Wikipedia, the free encyclopedia